Cultures of decolonisation: transnational productions and practices, 1945-70 - Craggs, Ruth; Wintle, Claire (Studies in imperialism, 2016)
Machine generated contents note: pt. I Decolonising metropolitan cultures? -- 1. Black America and the overthrow of the European colonial order: The tragic voice of Richard Wright / Bill Schwarz -- 2. Humanist modernism: Ralph Hotere and `New Commonwealth Internationalism' / Damian Skinner -- 3. Henry Swanzy, Sartre's zombie? Black Power and the transformation of the Caribbean Artists Movement / Rob Waters -- 4. Anxiety abroad: Austerity, abundance and race in post-war visual culture / David C. Wall -- pt. II Performing decolonisation -- 5. The peasant armed: Bengal, Vietnam and transnational solidarities in Utpal Dutt's Invincible Vietnam / Abin Chakraborty -- 6. Cultural heritage as performance: Re-enacting Angkorian grandeur in postcolonial Cambodia (1953 -- 70) / Michael Falser -- 7.`I still don't have a country': The southern African settler diaspora after decolonisation / Jean Smith -- pt. III Decolonising expertise